Sistemas de costos en el proceso productivo del sector cacaotero - Veintemilla Alba, Annabel Janina (2021)
This research paper named Cost Systems in the cocoa production process, aims to reflect what is the best alternative when it comes to pay for cocoa production. I took as reference several techniques used in research as the basis of the methodology, which helped to investigate the main problem, taking into consideration the type of mixed approach to adequately refer to the data found............